Software for the care of people with cardiovascular risk: construction and evidence of validity. - de Carvalho Félix, Nuno Damácio; Carneiro, Raércia dos Santos; Rasia Pacheco, Luis Filippe; Cunha, Brenda Silva; Neto, João Cruz; Boness, Johann Aires; Gavazza, Mariana Carvalho; Bottura Leite de Barros, Alba Lúcia (Revista Brasileira de Enfermagem, 2024)
Objectives: to build and validate software for the care of people with cardiovascular risk. Methods: a methodological study, applied to software development, anchored in a nursing theory and classification system, in three stages: 1) requirements engineering; 2) software architecture and coding; and 3) testing and content validity by 12 experts in computer science, with a Content Validity Ratio score. Results: called e-TEORISC, in software format, for nursing care for people with cardiovascular risk, online and offline, containing a database linked to the Nursing Process stages. Experts considered that the attributes of functional suitability, performance efficiency, reliability, maintainability, usability, safety and portability obtained desirable scores. Conclusions: e-TEORISC has evidence of validity to instrumentalize care for people at cardiovascular risk, with potential for technology transfer to the Brazilian Health System.